The Influence of Work-Life Balance on Work Engagement Through Job Stress and Job Satisfaction as Mediation in Construction Company Employees - Mustika, Klara; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (Jurnal Economic Resource, 2024)
This research aims to examine the influence of work-life balance on work engagement and work stress mediated by job satisfaction in state-owned companies in the construction sector. The research method used is descriptive quantitative research, using SEM techniques to see the direct and indirect effects of research variables. The data collection technique used was distributing questionnaires to 73 respondents (BUMN employees in the Construction sector from 3 PGN Work Units) selected proportionally by cluster random sampling. The results showed that work-life balance had a negative influence on work stress (r= -0.88; p<0.05), work-life balance had a positive influence on job satisfaction (r=0.59; p<0.05), work stress had a negative influence on engagement. work (r= -0.69; p<0.05). Furthermore, job satisfaction has a positive influence on work engagement (r= 0.90; p<0.05), and work-life balance influences work engagement (r=0.241; p<0.05). The work-life balance variable has a significant influence on work engagement through work stress (r= 0.487; p<0.05) and the work-life balance variable has a positive and significant effect on work engagement through job satisfaction (r= 0.069; p<0.05). The conclusion of this research is that job satisfaction is a mediating variable that contributes to a stronger influence of work-life balance on work engagement compared to the contribution of work stress as a mediating variable on the quality of work life.